Cause of death in HIV-infected patients in South Carolina (2005–2013). (January 2016) - Cima, Michael; Parker, R. David; Ahmed, Yasir; Cook, Sean; Dykema, Shana; Dukes, Kristina; Albrecht, Stephan; Weissman, Sharon
Summary: The life span of persons with HIV has been greatly extended over the past 30 years due to novel therapies. In the developed world and urban settings, this results in a lifespan rivaling the lifespan of a person without HIV. A retrospective study was conducted on 459 patients of an urban, academic medical center who died between 2005 and 2013 in a medium-sized US city. Using the established Cause of Death Project (CoDe) protocol, we measured multiple factors including comorbidities, risk behaviours, contributing and underlying causes of death. This study is one of the few US-based studies using this validated protocol. Among the deaths, 25.9% were sudden and 15.2% were unexpected. Almost one-fifth were related to AIDS-related infections; 47.5% related to non-AIDS causes; with the remainder unknown. Statistically significant increases in CD4 counts and decreasing viral loads were observed over the study period. There were no statistically significant differences observed by HIV risk behaviour, race, gender, age at death, or on antiretrovirals at death. In support of the existing literature, improved HIV management appears to reduce the AIDS-related attributable death among patients observed in this study.